L’epica queer di "Angels in America": Tecniche e strategie di scrittura - Pizzo, Antonio (Mimesis Journal, 2024)
The paper analyses the worldwide know Kushner’s masterpiece through the lens of a queer aesthetic. The play has been largely discussed in literature according the numbers of themes it contains. The article aims to show how those themes are part of LGBT culture and politics. Moreover, the article’s final goal is to verify how the basic elements of dramatic writing are handled by the author within a queer perspective. In the paly, the traditional features of the drama, such as, action, characters, conflict, are twisted and rendered in a specific way in order to quote (or to promote) a queer approach to writing. At the end, this can be read as the Kushner’s personal interpretation of political theatre, via a sort of queer epic theatre.